2005
DOI: 10.1152/jn.00280.2005
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Swallowing Performance in Intact, Freely FeedingAplysia

Abstract: Variability in nervous systems is often taken to be merely "noise." Yet in some cases it may play a positive, active role in the production of behavior. The central pattern generator (CPG) that drives the consummatory feeding behaviors of Aplysia generates large, quasi-random variability in the parameters of the feeding motor programs from one cycle to the next; the variability then propagates through the firing patterns of the motor neurons to the contractions of the feeding muscles. We have proposed that, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 69 publications
4
46
0
Order By: Relevance
“…There is considerable evidence that radula movements, which are organized in an all-or-none action pattern of protraction-retraction mouth closure, constitute a highly variable component of Aplysia feeding behavior (Horn et al, 2004;Jing et al, 2004;Jing and Weiss, 2005;Lum et al, 2005;Zhurov et al, 2005;Ye et al, 2006). We now show that the temporal structure of radula bite cycles during food seeking is also a flexible constituent of this behavior.…”
Section: Operant Conditioning and Induction Of Compulsive-like Feedinmentioning
confidence: 64%
See 1 more Smart Citation
“…There is considerable evidence that radula movements, which are organized in an all-or-none action pattern of protraction-retraction mouth closure, constitute a highly variable component of Aplysia feeding behavior (Horn et al, 2004;Jing et al, 2004;Jing and Weiss, 2005;Lum et al, 2005;Zhurov et al, 2005;Ye et al, 2006). We now show that the temporal structure of radula bite cycles during food seeking is also a flexible constituent of this behavior.…”
Section: Operant Conditioning and Induction Of Compulsive-like Feedinmentioning
confidence: 64%
“…We next analyzed the temporal organization of the more frequent radula biting after appetitive training. It was reported previously that, during active consumption of long strips of seaweed, radula movements are expressed in a rhythmic pattern, i.e., with regular intervals between successive protraction/retraction cycles (Kupfermann, 1974) (but see Lum et al, 2005). During foodseeking behavior that preceded reward stimulation, however, we found that only a small proportion of animals (control, 0 of 10; seaweed, 1 of 10; cellulose, 2 of 10) generated such rhythmic biting (as defined by autocorrelation analysis) and that these proportions were not significantly different among the three animal groups (control vs seaweed, P ϭ 1; seaweed vs cellulose, P ϭ 1; control vs cellulose, P ϭ 0.47).…”
Section: Food Intake Modifies Triggering Of Radula Bite Cyclesmentioning
confidence: 99%
“…Conversely, the weak correlation when B64 latencies were negative is consistent with the idea that the B64-independent means of protraction termination may make an important contribution to protraction termination when B64 is hyperpolarized, and these B64-independent actions are not highly correlated with how negative B64 latencies are. Also, if one considers that, under control conditions, B64 latencies are on the order of tens of milliseconds, whereas hyperpolarizations of B64 extend the duration of protractions by Ͼ10 s, it is perhaps not surprising that, given the biological variability in the feeding system of Aplysia (Horn et al, 2004;Lum et al, 2005;Ye et al, 2006;Nargeot et al, 2007), the correlation was weak.…”
Section: B64 Latency In Intermediate Programsmentioning
confidence: 99%
“…In the Aplysia feeding system, these coordinations are well documented at the level of activity in identified interneurons, whereas for turtle scratch and hind limb swimming movements different couplings between pattern-generating modules are postulated. In both cases, however, although distinct switches in coordinations are observed, much emphasis has been placed on the demonstration that intermediate coordination states exist and even grade into one another and that the realization of coordination mode is determined by internal state and sensory stimulation, e.g., seemingly more by the site of irritation in the case of turtle scratch (Stein 2005) and more by internal state (sensory history) in the case of Aplysia feeding (Lum et al 2005;Zhurov et al 2005). Indeed in the hind limb of the turtle even hybrids between scratch and hind limb swimming patterns are observed.…”
Section: Stereotypy and Phase Constancy In Central Pattern Generator mentioning
confidence: 99%